2019
DOI: 10.1002/tox.22759
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA‐ENST00000501520 promotes the proliferation of malignant‐transformed BEAS‐2B cells induced with coal tar pitch mediated by target genes

Abstract: As a human carcinogen, coal tar pitch (CTP) can significantly increase the risk of lung cancer. However, the mechanism underlying CTP‐induced lung carcinogenesis has not been well understood. This study aims to explore the role of the LncRNA‐ENST00000501520 in the proliferation of malignant‐transformed human bronchial epithelial cells (BAES‐2B) induced by CTP extract for the first time. BEAS‐2B cells were stimulated with 2.4 μg/mL CTP extract, and then passaged for three times, which were named passage 1 and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Consistent with our results, the expression of SBK1 was facilitated by LncRNA ELFN1‐AS1 to promote proliferation and invasion in retinoblastoma 15 . SBK1 was also activated in the malignant transformation of pulmonary epithelial cells 16 . Deleterious mutations in SBK1 were pinpointed in the metastasis of acral melanoma by WES 17 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with our results, the expression of SBK1 was facilitated by LncRNA ELFN1‐AS1 to promote proliferation and invasion in retinoblastoma 15 . SBK1 was also activated in the malignant transformation of pulmonary epithelial cells 16 . Deleterious mutations in SBK1 were pinpointed in the metastasis of acral melanoma by WES 17 .…”
Section: Discussionsupporting
confidence: 88%
“…15 SBK1 was also activated in the malignant transformation of pulmonary epithelial cells. 16 Deleterious mutations in SBK1 were pinpointed in the metastasis of acral melanoma by WES. 17 Li et al 18 identified that SBK1 was upregulated in ovarian cancer cells and was associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In PC9 cells, Gefitinib could promote FBP1 expression and inhibit SBK1 and AURKA levels. An increasing body of evidence suggests that FBP1, SBK1 and AURKA are associated with lung cancer progression [10][11][12][13][14][15]. For instance, FBP1 was found to be downregulated in lung cancer tissues and cells.…”
Section: Discussionmentioning
confidence: 99%
“…Upon inhibition of long non-coding RNA ENST000001520 in BEAS-2B cells, a notable decrease is observed in cell migration and proliferation abilities, accompanied by an increase in apoptosis capabilities. These changes can be attributed to the downregulation of SBK1 and SOCS3 mRNA and protein expression [ 14 ]. This finding indicated that Gefitinib could affect FBP1, SBK1 and AURKA expression to inhibit LUAD progression.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no significant difference in the expression of GNAO1 and KSR2 between tumor and paracancerous tissue samples. Meanwhile, both SBK1 and SLIT3 were found to play a vital role in lung cancer by miRNA or lncRNA [49][50][51]. Thereinto, we focused on ZC3H12D to construct a ceRNA regulatory network, and screened for potentially functional miRNAs and lncRNAs (Fig.…”
Section: Construction Of Cerna Regulatory Network In Luadmentioning
confidence: 99%